Delivery of Bone Marrow-Derived Mesenchymal Stem Cells Improves Tear Production in a Mouse Model of Sjögren's Syndrome. (2nd March 2017) - Aluri, Hema S.; Samizadeh, Mahta; Edman, Maria C.; Hawley, Dillon R.; Armaos, Helene L.; Janga, Srikanth R.; Meng, Zhen; Sendra, Victor G.; Hamrah, Pedram; Kublin, Claire L.; Hamm-Alvarez, Sarah F.; Zoukhri, Driss
Abstract : The purpose of the present study was to test the potential of mouse bone marrow-derived mesenchymal stem cells (BD-MSCs) in improving tear production in a mouse model of Sjögren's syndrome dry eye and to investigate the underlying mechanisms involved. NOD mice (n = 20 ) were randomized to receive i.p. injection of sterile phosphate buffered saline (PBS, control) or murine BD-MSCs (1 × 10 6 cells). Tears production was measured at baseline and once a week after treatment using phenol red impregnated threads. Cathepsin S activity in the tears was measured at the end of treatment. After 4 weeks, animals were sacrificed and the lacrimal glands were excised and processed for histopathology, immunohistochemistry, and RNA analysis. Following BD-MSC injection, tears production increased over time when compared to both baseline and PBS injected mice. Although the number of lymphocytic foci in the lacrimal glands of treated animals did not change, the size of the foci decreased by 40.5% when compared to control animals. The mRNA level of the water channel aquaporin 5 was significantly increased following delivery of BD-MSCs. We conclude that treatment with BD-MSCs increases tear production in the NOD mouse model of Sjögren's syndrome. This is likely due to decreased inflammation and increased expression of aquaporin 5.